2020
DOI: 10.1155/2020/7041520
|View full text |Cite
|
Sign up to set email alerts
|

Maspin, Syndecan-1, and Ki-67 in the Odontogenic Keratocyst: An Immunohistochemical Analysis

Abstract: The odontogenic keratocyst (OKC) is a controversial lesion that was reclassified as a tumor with the name “keratocystic odontogenic tumor” in 2005. The reclassification was revoked recently in 2017, with a conclusion on the need for further studies on the subject. In this study, the expressions of an important regulatory protein (maspin), an important integral membrane proteoglycan (syndecan-1), and a universal proliferation marker (Ki-67) in the epithelium of the OKC were investigated in comparison with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 60 publications
1
16
0
1
Order By: Relevance
“…The same distribution was described in previous studies employing ki-67 which is a known proliferation marker reported to be present during all active phases of the cell cycle and absent in the quiescent cells. [14][15][16] The currently observed localization stands in a line with previous studies suggesting that the peripheral cells might have an important role in the proliferative activity of Am neoplasm. Further support to this notion is provided by studies that reported that mutated p53; a tumor suppressor gene was mostly located in the peripheral columnar cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The same distribution was described in previous studies employing ki-67 which is a known proliferation marker reported to be present during all active phases of the cell cycle and absent in the quiescent cells. [14][15][16] The currently observed localization stands in a line with previous studies suggesting that the peripheral cells might have an important role in the proliferative activity of Am neoplasm. Further support to this notion is provided by studies that reported that mutated p53; a tumor suppressor gene was mostly located in the peripheral columnar cells.…”
Section: Discussionsupporting
confidence: 91%
“…The current result agrees with other studies employing the ki-67 which showed weak reactivity in the basal and suprabasal cells of the epithelial lining of DC. 16,20 This reflects the low activity in the proliferative component of the lining and consequently the known indolent course of DC. 3,5,16,21,22 An original finding in our research is the dual staining pattern, nuclear and cytoplasmic, with a predominance of the former pattern in the Am group of neoplastic nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontogenic cysts belong to a heterogeneous group of lesions that constitute innocuous inflammatory cysts to develop cysts, sometimes behave in a locally aggressive manner, and may show variegated histologic morphologies 10 . The OKCs are aggressive cystic jaw lesions with an increased propensity for recurrence and have a high growth potential 1 . Marsupialization is a treatment of choice used by surgeons to reduce the volume of OKCs before enucleation and minimize vascular and neurological complications, unesthetic outcomes, and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…O nível de expressão aumenta na fase G1 para a mitose e, em seguida, diminui ou desaparece logo após a mitose. Tais características o tornam um excelente marcador para determinar a chamada fração de crescimento e status de proliferação de uma determinada população(83)(84)(85)(86)(87)(88)(89). por exemplo.…”
unclassified